A non‐isolated high step‐up DC‐DC converter with integrated 3 winding coupled inductor and reduced switch voltage stress. (30th May 2018) - Mahmoudi, Mohsen; Ajami, Ali; Babaei, Ebrahim
Summary: In this paper, a non‐isolated high step‐up dc‐dc converter based on coupled inductor is proposed. The proposed converter can be used in renewable energy applications. In suggested converter, the high voltage is achieved using 3‐winding coupled inductor, which leads to low voltage rate of the switch. A clamp circuit is used to recycle the leakage inductance energy. Also, the clamp circuit prevents the creation of voltage spikes on semiconductor devices and causes the voltage stress of elements are limited to less than the output voltage. The presented theoretical analyses show that the operation of suggested converter in continuous conduction mode needs to small magnetic inductor. Therefore, the size of coupled inductor's core is reduced, and so the size and cost of presented converter will be decreased. Analysis of the proposed converter is provided with laboratory results to verify its performance. Abstract : In this paper, a non‐isolated high step‐up dc‐dc converter based on coupled inductor is proposed. The proposed converter can be used in renewable energy applications. In proposed converter, the high voltage is achieved using 3‐winding coupled inductor, which leads to low voltage rate of the switch. A clamp circuit is used to recycle the leakage inductance energy. Also, the clamp circuit prevents the creation of voltage spikes on semiconductor devices.